Chronic urticaria and coagulation: pathophysiological and clinical aspects. Issue 6 (27th March 2014) - Tedeschi, A.; Kolkhir, P.; Asero, R.; Pogorelov, D.; Olisova, O.; Kochergin, N.; Cugno, M.
Abstract Chronic urticaria (CU) is a widespread skin disease, characterized by the recurrence of transient wheals and itch for more than 6 weeks. Besides autoimmune mechanisms, coagulation factors, in particular tissue factor and thrombin, might also participate in the disease pathophysiology. Tissue factor expressed by eosinophils can induce activation of blood coagulation generating thrombin which in turn can increase vascular permeability both directly, acting on endothelial cells, and indirectly, inducing degranulation of mast cells with release of histamine, as demonstrated in experimental models. D‐dimer, a fibrin degradation product, generated following activation of the coagulation cascade and fibrinolysis, has been found to be increased during urticaria exacerbations; moreover, it has been proposed as a biomarker of severity and resistance to H1‐antihistamines in CU patients. The possible role of coagulation in CU is also supported by case reports, case series and a small controlled study showing the efficacy of anticoagulant therapy in this disease. The purpose of this review was to summarize the available data on the possible contribution of coagulation to the pathophysiology of CU focusing on clinical aspects and possible future therapeutic developments.